The rubber hand illusion induced by visual-thermal stimulation - Trojan, Jörg; Fuchs, Xaver; Diers, Martin (Scientific reports, 2018)
In the rubber hand illusion (RHI), synchronous touch of a real hand and an artificial hand leads to the feeling of the artificial hand belonging to one’s own body. This study examined whether the RHI can be induced using visual-thermal instead of visual-tactile stimulus patterns and to which extent the congruency between temperature and colour of the visual stimulus influences the RHI. In a within-subject design, we presented cold vs. warm thermal stimuli to the participants’ hidden hand combined with red vs. blue visual stimuli presented synchronously vs. asynchronously at a fake hand. The RHI could be induced using visual-thermal stimuli, yielding RHI vividness ratings comparable to the visual-tactile variant. Congruent (warm-red, cold-blue) synchronous stimulus patterns led to higher RHI vividness than incongruent (warm-blue, cold-red) synchronous combinations; in the asynchronous conditions, an inverse effect was present. Temperature ratings mainly depended on the actual stimulus temperature and were higher with synchronous vs. asynchronous patterns; they were also slightly higher with red vs. blue light, but there were no interactions with temperature or synchrony. In conclusion, we demonstrated that the RHI can be induced via visual-thermal stimuli, opening new perspectives in research on multi-sensory integration and body representations.